2012
DOI: 10.2164/jandrol.110.012666
|View full text |Cite
|
Sign up to set email alerts
|

Combined Strategy of Mesenchymal Stem Cell Injection With Vascular Endothelial Growth Factor Gene Therapy for the Treatment of Diabetes‐Associated Erectile Dysfunction

Abstract: This study was designed to investigate the effect of vascular endothelial growth factor 164 adenovirus (Ad-VEGF 164 )-transfected mesenchymal stem cells (MSC) on improving erectile function in diabetic rats. Forty-five male Sprague-Dawley rats were injected with streptozotocin to develop type 1 diabetes, whereas 10 served as normal controls. Diabetic rats were randomly divided into 3 groups: rats that underwent intracavernous injection with phosphatebuffered saline (DM+PBS), unmodified MSCs (DM+MSC), and Ad-VE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
78
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 42 publications
(45 reference statements)
0
78
1
Order By: Relevance
“…Some studies confirmed that embryonic stem cells can be used for the treatment of neurogenic ED (Eglitis and Mezey 1997). Studies of the effect of mesenchymal (Bivalacqua et al 2007;Qiu et al 2012), human neural crest (Song et al 2008), and adipose tissue-derived stem cells (Albersen et al 2010;Garcia et al 2010;Huang et al 2010) on ED treatment have also been performed by other researchers using intracavernous injection of these cells in rats. The results indicated that ED could be improved to a certain extent when treated with these cells.…”
Section: Introductionmentioning
confidence: 96%
“…Some studies confirmed that embryonic stem cells can be used for the treatment of neurogenic ED (Eglitis and Mezey 1997). Studies of the effect of mesenchymal (Bivalacqua et al 2007;Qiu et al 2012), human neural crest (Song et al 2008), and adipose tissue-derived stem cells (Albersen et al 2010;Garcia et al 2010;Huang et al 2010) on ED treatment have also been performed by other researchers using intracavernous injection of these cells in rats. The results indicated that ED could be improved to a certain extent when treated with these cells.…”
Section: Introductionmentioning
confidence: 96%
“…Because stem cells can directionally differentiate into corpus cavernosum vascular endothelial cells and smooth muscle cells under a specific microenvironment, the transplantation of stem cells for treating diabetic ED was proposed as a potential therapeutic approach [8][9][10] . Mesenchymal stem cells (MSCs) have been tested in transplantation therapy for diabetic ED [11][12][13] . Although stem cell transplantation can improve erectile function in animal studies, the effect last only 7-28 d before gradually diminishing [14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…Actually no safety system has been inserted in the MSCs to eliminate them when excessively proliferating, no selective genetic insertion has been reported, thus increasing oncogenic risk. Moreover, no solution has been added to overcome problems like virus spread and reversion to its original form [Qiu et al 2012].…”
Section: Stem Cellsmentioning
confidence: 99%